DYNAMICS OF CRUISE SHIP TOURIST SERVICE MANAGEMENT AT BONDJAVA TRAVEL TOURS IN SEMARANG AND SURABAYA CITIES - I Nyoman Sudirman; Sony Heru Priyanto; Sarbini Sarbini (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
The increasing number of cruise tourist arrivals at Tanjung Emas Port in Semarang and Tanjung Perak Port in Surabaya requires travel agencies to implement professional and well-structured operational management. However, field findings reveal gaps between Standard Operating Procedures (SOPs) and their actual implementation at Bondjava Travel Tours, which affect service quality. This study analyzes the dynamics of operational management in handling cruise tourists, covering planning, implementation, supervision, operational challenges, and response strategies. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observations, and document analysis conducted in Semarang and Surabaya. The results show that Bondjava Travel Tours has established structured planning and coordination mechanisms; however, several challenges remain, particularly in the consistency of SOP implementation, the quality of human resources, the readiness of transportation facilities, and coordination among service providers. These constraints influence the effectiveness of service delivery and the overall tourist experience.The findings highlight the importance of strengthening quality control systems, improving human resource competencies, and enhancing integration within the tourism service supply chain. Therefore, strategic efforts are needed, including refining more applicable SOPs, intensifying human resource training, strengthening coordination among stakeholders, and implementing continuous monitoring systems. These measures are expected to improve operational effectiveness and support the sustainability of cruise tourism services.